Analysis and Structural Identification of the Flavonoid Compounds in Fruit of Citrus reticulata Blanco cv. Ougan from China - Li, Yu-Xian; Chen, Xiang-Tao; Liu, Hua-Liang; Yuan, Ke (Asian Journal of Chemistry, 2011)
Using the fruit of Citrus reticulata Blanco cv. Ougan from the different regions of Zhejiang Province, China, as object, this research separated and identified the compounds of flavonoid in C. ougan fruit, meanwhile, we also determined the content of the three glycosylflavones in C. ougan fruit by the method of HPLC. This study used the method of column chromatography of sephadex LH-20, RP 18 and silica gel to separate and purify and thus elucidated 8 kinds of chemical compounds by the physicochemical properties and spectral data and identify the structures of the compounds. The 8 compounds were named as: eugenol (1), hesperetin (2), b- sitosterol (3), succinic acid (4), neohesperidin (5), hesperidin (6), naringin (7), naringenin (8). The above compounds are obtained for the first time by separation from the new species of C. ougan fruit. Using the above separated three monomer compounds i.e., hesperidin, neohesperidin and naringin as the reference substances, the research made a content determination of the three glycosylflavones in C. ougan fruit produced in different regions of Zhejiang Province by HPLC. The experimental results show that the content of the three glycosylflavones in the C. ougan fruit of different regions vary remarkably. The content of neohesperidin in the C. ougan fruit is the highest, the content of neohesperidin is more than naringin, over 10 times almost. The content of hesperidin is the lowerest in C. ougan fruit. The content of the three glycosylflavones in pericarp are all higher than those in pulp. From these studies, it is suggested that there are rich glycosylflavones in the C. ougan fruit from China.